Co-Curriculum Activities and National Integration During the Movement Control Order in Malaysia - Kaspin, Khairul Ghufran; Hamzah, Intan Suria; Abdullah, Mohd Syariefudin; Marzuki, Mazdi; Razali, Nur Azah (SCAD Independent, 2024)
In Malaysia, school activities were disrupted from 2020-2021 due to the enforcement of the Movement Control Order (MCO) in response to the COVID-19 pandemic that hit the country. It caused many things to be temporarily disrupted including co-curriculum activities at school. Therefore, this study was conducted to examine pupils’ perceptions of the co-curriculum activities carried out by the school during the MCO and the effect of those activities on national integration among the pupils. It was quantitative research using a set of questionnaires as its research instrument. The research location was at Tanjong Malim, Perak, Malaysia where five secondary schools were selected. A total of 487 pupils, consisting of 243 Form two pupils and 244 pupils Form four pupils represented various ethnic and religious backgrounds. As a result, the study found that the national integration process was incorporated well through the co-curriculum activities even though the activities were conducted through online mediums. Overall, the score level was High for the majority of the results. Thus, it showed that even though the implementation of MCO had limited the process of national integration through co-curriculum activities, however, the implementation went well. The difference was, that the co-curriculum activities were conducted through online methods.